Diaphragm electromyographic activity following unilateral midcervical contusion injury in rats - Rana, Sabhya (J Neurophysiol, 2016)
Contusion-type injuries to the spinal cord are characterized by tissue loss and disruption of spinal pathways. Midcervical spinal cord injuries impair the function of respiratory muscles and may contribute to significant respiratory complications. This study systematically assessed the impact of a 100-kDy unilateral C4 contusion injury on diaphragm muscle activity across a range of motor behaviors in rats. Chronic diaphragm electromyography (EMG) was recorded before injury and at 1 and 7 days postinjury (DPI). Histological analyses assessed the extent of perineuronal net formation, white-matter sparing, and phrenic motoneuron loss. At 7 DPI, ∼45% of phrenic motoneurons were lost ipsilaterally. Relative diaphragm root mean square (RMS) EMG activity increased bilaterally across a range of motor behaviors by 7 DPI. The increase in diaphragm RMS EMG activity was associated with an increase in neural drive (RMS value at 75 ms after the onset of diaphragm activity) and was more pronounced during higher force, nonventilatory motor behaviors. Animals in the contusion group displayed a transient decrease in respiratory rate and an increase in burst duration at 1 DPI. By 7 days, following midcervical contusion, there was significant perineuronal net formation and white-matter loss that spanned 1 mm around the injury epicenter. Taken together, these findings are consistent with increased recruitment of remaining motor units, including more fatigable, high-threshold motor units, during higher force, nonventilatory behaviors. Changes in diaphragm EMG activity following midcervical contusion injury reflect complex adaptations in neuromotor control that may increase the risk of motor-unit fatigue and compromise the ability to sustain higher force diaphragm efforts. NEW & NOTEWORTHY The present study shows that unilateral contusion injury at C4 results in substantial loss of phrenic motoneurons but increased diaphragm muscle activity across a range of ventilatory and higher force, nonventilatory behaviors. Measures of neural drive indicate increased descending input to phrenic motoneurons that was more pronounced during higher force, nonventilatory behaviors. These findings reveal novel, complex adaptations in neuromotor control following injury, suggestive of increased recruitment of more fatigable, high-threshold motor units.